Mechanical properties of compliant double layered poly(L-lactide-co-epsilon-caprolactone) vascular graft - Kim, Sang-Hoon; Mun, Cho Hay; Jung, Youngmee; Kim, Sang-Heon; Kim, Dong-Ik; Kim, Soo Hyun (SPRINGER, 2013)
We fabricated a tubular double-layered scaffold using two steps; poly(L-lactide-co-E >-caprolactone) (PLCL) gel spinning method and salt leaching. The objective of the present study was to characterize the mechanical properties of tubular double-layered PLCL scaffolds that had different wall thickness values. We evaluated the bio-vascular scaffold in terms of cardiovascular implants-tubular vascular prostheses in international standard; ANSI/AAMI/ISO 7198:1998/2001. According to the ISP 7198, PLCL had sufficient mechanical strength, burst strength, tensile strength to withstand blood pressure and had similar compliance to native vessels due to its elasticity. We applied the tubular vascular prostheses' evaluation method using an existing surgical operation. The vascular scaffold, which had a similar compliance to native vessels, did not result in severe thrombosis in vivo for 4 weeks. Thus, this novel material holds great promise for use as a blood vessel substitute.
Keywords: COMPLIANCE MISMATCH; TUBULAR SCAFFOLDS; PLCL SCAFFOLDS; TISSUE; POLYCAPROLACTONE; ARTERIES; BEHAVIOR; ELASTIN; PATENCY; FIBERS